Origin of Mass - Paudel, Eak Raj (BMC Journal of Scientific Research, 2018)
Thousands of physicists are working night and day to solve an even more fundamental problem. How do particles acquire mass? Although many of us would like to have less mass, particle theorists find it extremely difficult to explain how we have any at all. In this paper I attempt to explain the formation of mass by different approaches which may clarify the concept of mass.